Frequency of Left Ventricular Thrombus after Acute Anterior Wall Myocardial Infarction at Karachi - Fiyaz Hussain Mallah, Muhammad Tariq, Waqar Hussain, Javed Khurshed Shaikh, Muhammad Hassan Butt, M. Ismail Baloch (Pakistan Journal of Medical & Health Sciences, 2022)
Background: The left ventricular problem is a prominent acute myocardial infarction (AMI) complication. It has been demonstrated that rapid reperfusion reduces mortality and improves left ventricular (LV) function. There is a dearth of information on left ventricular thrombus (LVT) in the current era of primary percutaneous coronary intervention (PPCI). Aim: To estimate the frequency of left ventricular thrombus in patients who have experienced an acute anterior wall myocardial infarction at Karachi’s leading cardiac hospital. Study design: Cross-sectional study Place and duration of study: Department of Cardiology, National Institute of Cardiovascular Disease, Karachi from 1st July 2021 to 31st December 2021. Methodology: Three hundred and fifty five patients of both genders age between 40 and 80 years were diagnosed with acute anterior wall myocardial infarction and underwent purcutaneous coronary intervention were enrolled. Results: There were 286 (80.6%) males and 69 (19.4%) females. The mean age was 56.29±11.04 years. Two patients (6%) experienced in-hospital mortality, while 56 patients (15.8%) had left ventricular thrombus. Conclusion: Acute ST-elevation myocardial infarction frequently results in the development of left ventricular thrombus. Keywords: Myocardial infarction, Left ventricular thrombus, Frequency